On the validity of the ambipolar diffusion assumption in the polar mesopause region - A. P. Ballinger; P. B. Chilson; R. D. Palmer; N. J. Mitchell (Annales Geophysicae, 2008)
The decay of underdense meteor trails in the polar mesopause region is thought to be predominantly due to ambipolar diffusion, a process governed by the ambient temperature and pressure. Hence, observations of meteor decay times have been used to indirectly measure the temperature of the mesopause region. Using meteor observations from a SKiYMET radar in northern Sweden during 2005, this study found that weaker meteor trails have shorter decay times (on average) than relatively stronger trails. This suggests that processes other than ambipolar diffusion can play a significant role in trail diffusion. One particular mechanism, namely electron-ion recombination, is explored. This process is dependent on the initial electron density within the meteor trail, and can lead to a disproportionate reduction in decay time, depending on the strength of the meteor.